Finding God's will for your life : discovering the plans God has for you - Meyer, Joyce, 1943- (FaithWords, 2024)
"Did you ever dream about what you would be when you grew up? We think naturally about our purpose because God tells us that He created us to do great things. But how do we know when we have truly found God's calling for our lives? Many people live most of their lives striving to find and follow God's will but still wondering whether they've gotten it right. The many pressures, expectations, and distractions we experience can create confusion and anxiety and cause us to doubt whether we are following God's will or if He even has a plan for us at all. Beloved Bible teacher Joyce Meyer invites us on a journey to confidence, freedom, and peace through exploring the wisdom of what the Bible tells us about God's character and about His love and purpose for us. She also offers practical steps to discovering how to build your trust in God, seek His guidance, and overcome the fear of missing out on His best for you. If you're struggling to have confidence that you can hear God's voice and know what He's created you to be and do, Finding God's Will for Your Life will leave you with more peace and more confidence to live joyfully in God's love and walk the path He has for you"--